2009
DOI: 10.1051/0004-6361/200911859
|View full text |Cite
|
Sign up to set email alerts
|

The CN isotopic ratios in comets

Abstract: Our aim is to determine the isotopic ratios 12 C/ 13 C and 14 N/ 15 N in a variety of comets and link these measurements to the formation and evolution of the solar system. The 12 C/ 13 C and 14 N/ 15 N isotopic ratios are measured for the CN radical by means of high-resolution optical spectra of the R branch of the B-X (0, 0) violet band. 23 comets from different dynamical classes have been observed, sometimes at various heliocentric and nucleocentric distances, in order to estimate possible variations of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
89
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 45 publications
19
89
0
Order By: Relevance
“…Isotopic ratios have proven extremely powerful in providing quantitative constraints on the composition of the protosolar disk from which the solar system formed (Chaussidon & Gounelle 2007;Jehin et al 2009). For carbon, the isotopic ratio 12 C/ 13 C measured in comets shows a remarkable homogeneity, with a mean value of 91 that agrees with the solar value of 90, and is also very close to the value of 70 determined in the local ISM (Milam et al 2005;Asplund et al 2009;Manfroid et al 2009). For oxygen, measurements in comets lead to 16 O/ 18 O ratios between 500 and 600, which again are in good agreement with the solar and local ISM value of 500 (Wilson & Rood 1994).…”
Section: Introductionsupporting
confidence: 77%
“…Isotopic ratios have proven extremely powerful in providing quantitative constraints on the composition of the protosolar disk from which the solar system formed (Chaussidon & Gounelle 2007;Jehin et al 2009). For carbon, the isotopic ratio 12 C/ 13 C measured in comets shows a remarkable homogeneity, with a mean value of 91 that agrees with the solar value of 90, and is also very close to the value of 70 determined in the local ISM (Milam et al 2005;Asplund et al 2009;Manfroid et al 2009). For oxygen, measurements in comets lead to 16 O/ 18 O ratios between 500 and 600, which again are in good agreement with the solar and local ISM value of 500 (Wilson & Rood 1994).…”
Section: Introductionsupporting
confidence: 77%
“…heavily enriched in 15 N) that obtained for HCN (e.g. Arpigny et al 2003;Manfroid et al 2009;Hutsemékers et al 2005;Bockelée-Morvan et al 2008). This differential between radio and visible measurements extended to Hale-Bopp (Arpigny et al 2003), which had already been shown to have a consistent isotopic ratio for carbon, as discussed above.…”
Section: Nitrogen Isotopessupporting
confidence: 61%
“…Of these, the CN and HCN measurements are the most extensive (e.g. Manfroid et al 2009), while C 2 measurements have the longest history (e.g. Danks et al 1974;Vanysek 1973;Owen 1973;Lambert and Danks 1983), extending from comet Ikeya (1963a) (Stawikowski and Greenstein 1964) through comet C/2002 T7 (LINEAR) (Rousselot et al 2012).…”
Section: Carbon Isotopesmentioning
confidence: 99%
See 2 more Smart Citations